HELP-SEEKING AND PERCEIVED HELPFULNESS OF FORMAL HELP SOURCES FOR VICTIMS OF DOMESTIC VIOLENCE: AN EXPLORATORY STUDY - Zuzana Vasiliauskaite (European Scientific Journal, ESJ, 2015)
The aim of this study is to gain an understanding of domestic violence victims’ help-seeking behavior and what they consider to be most helpful, taking into account legal changes such as criminalization of domestic violence (DV) and additional formal help sources available to the victims. Data was collected through semi-structured interview of five women that sought help from Vilnius City Specialized Help Centre (SHC) for DV victims. PTSD Symptom Scale—Self Report version five (PSS-SR5) was applied to determine the impact of domestic violence on a persons’ wellbeing. Results were driven from thematic data analysis of in-depth semi-structured interviews and were presented as themes. Results suggest that all women sought help from formal help sources such as police, intervention centers (Specialized Help Centers), and from medical and social services. The most helpful formal help source they found was from SHCs. In carrying out the State delegated function, they provided the best assistance and therefore rekindle the trust in the legal system as well as the State itself. All women experienced institutional violence and/or institutional betrayal. According to the results of PSS-SR5, high scores of post-traumatic stress disorder were the characteristics of the participants. Results can be used to enhance the knowledge of the women’s experience and their perception on what services are the most helpful. In addition, the result of this study is relevant to professionals working with domestic violence victims, policy makers, as well as scholars.